HOUSING 21: Transformation as an Architectural Response - Živković, Milica; Stoiljković, Branislava; Keković, Aleksandar (Arhitektura i urbanizam, 2022)
The International Exhibition of Contemporary Housing – HOUSING 21, organized by the Department of Housing at the Faculty of Civil Engineering and Architecture, University of Niš, and the Cluster of Urban Planning presents a unique review of current trends in residential architecture, with a special focus on the concept of transformation and its multifaceted and multilayered implementation. By promoting representative and inspiring projects and realizations in defined thematic frameworks, and shaping and directing architectural discourses through interaction, networking, sharing and disseminating professional experiences, this biennial exhibition has gained the status of being a very important event for the professional community in Serbia. The paper is a review of the exhibition through the presentation of its program and accompanying activities, summarizing general impressions, experiences and results.